Integración e Implementación de un Sistema Interfaz Hombre Máquina Para Pruebas de Variadores de Media Tensión en la Empresa WEG Colombia (2022)
The following project was based on implementing and integrating a human-machine interface control system for the inspection process and final tests of medium voltage drives that allowed: visualization, measurement, control and analysis in the company WEG Colombia. Since in the process of reviewing and testing the finished product in medium voltage drives, the data of electrical variables such as current, power, harmonics, temperatures and voltages, etc. They were not collected automatically but manually, having as a consequence: influence of systematic errors, increases in execution times, decentralization of information and security to collect data. Therefore, different theoretical references were consulted that allowed documenting the project such as Human Machine Interface (HMI), Programmable Logic Control, Communication Networks and Communication Protocols. Regarding the methodological development, it was carried out through six phases: the first phase was based on device characterization and programming; the second phase consisted of HMI programming; the third phase, Modbus Protocol implementation; the fourth phase, elaboration of control diagrams; the fifth phase is parameterization of variables; finally, the sixth phase, evaluation and diagnosis. Finally, through the analysis of results, it was shown that there is an improvement in data collection times by having migrated from manual formats to the collection of information automatically generated by the HDMI.